Metaphor In Malay and Uzbek Cross-Culture - Azim Abdurakhmanovich Yuldashev (Euro Asian Journal Publishing, 2023)
The study of metaphors is increasing among the language masters, whether in literature, culture or other fields of life. However, the study of animal metaphors found in the proverbs has not yet been carried out
Keywords: Metaphor; Language; Uzbek